Development of once per revolution sensor chatter - Edzamila, Dzaidi (2013)
This research focused on the experimental development of once per revolution sensor chatter. In milling operation, self excited vibrations also called the chatter are one of the main factors that limit productivity. The project is used sensor chatter and non-sensor chatter to measure the variance of the signal sampled at a once per revolution rate. The sensor chatter is one of the main factors that lower the productivity. Higher efforts tend to accelerate tool wear and can lead to tool breakage. This project used the accelerometer to measures vibration and proper acceleration. The mounting of an accelerometer is easy but it is location must be carefully chosen. Indeed, if the sensor is close to a vibration node, signal amplitude would be very low. It is very difficult to put accelerometer on a rotating part. Beside that, the sensor tachometer (RPM gauge) is an instrument measuring the rotation speed of a tool milling machine. The device usually displays the revolutions per minute (RPM) on a calibrated analogue dial, but for this project the software of DasyLab that used can convert to revolution per second (RPS). A fast Fourier transform (FFT) is an algorithm to compute the discrete Fourier transform (DFT) and it is inverse. The result means the FFT operation, periodic functions will include changing the peak is not one, but two places. However, both these components are symmetric, so it was only necessary to see one to obtain frequency information. And providing information about the frequency, the FFT can be used to apply signal processing techniques such as filtering the signal and image compression is much easier to implement in the frequency domain. Detection of chatter, non-chatter and marginal chatter clearly can see in accelerometer, FFT and once per revolution signal. According to the results of machining experiment, it was proven that different parameter like spindle speed, feed rate and depth of cut producing chatter vibration.